The unique Katugin rare-metal deposit (southern Siberia): Constraints on age and genesis - Gladkochub, D.; Donskaya, T.; Sklyarov, E.; Kotov, A.; Vladykin, N.; Pisarevskiy, Sergei; Larin, A.; Salnikova, E.; Saveleva, V.; Sharygin, V.; Starikova, A.; Tolmacheva, E.; et al. (Elsevier Science BV, 2017)
© 2017 Elsevier B.V. We report new geological, mineralogical, geochemical and geochronological data about the Katugin Ta-Nb-Y-Zr (REE) deposit, which is located in the Kalar Ridge of Eastern Siberia (the southern part of the Siberian Craton). All these data support a magmatic origin of the Katugin rare-metal deposit rather than the previously proposed metasomatic fault-related origin. Our research has proved the genetic relation between ores of the Katugin deposit and granites of the Katugin complex. We have studied granites of the eastern segment of the Eastern Katugin massif, including arfvedsonite, aegirine-arfvedsonite and aegirine granites. These granites belong to the peralkaline type. They are characterized by high alkali content (up to 11.8wt% Na 2 O+K 2 O), extremely high iron content (FeO * /(FeO * +MgO)=0.96-1.00), very high content of most incompatible elements - Rb, Y, Zr, Hf, Ta, Nb, Th, U, REEs (except for Eu) and F, and low concentrations of CaO, MgO, P 2 O 5 , Ba, and Sr. They demonstrate negative and CHUR-close eNd(t) values of 0.0...-1.9. We suggest that basaltic magmas of OIB type (possibly with some the crustal contamination) represent a dominant part of the granitic source. Moreover, the fluorine-enriched fluid phases could provide an additional source of the fluorine. We conclude that most of the mineralization of the Katugin ore deposit occurred during the magmatic stage of the alkaline granitic source melt. The results of detailed mineralogical studies suggest three major types of ores in the Katugin deposit: Zr mineralization, Ta-Nb-REE mineralization and aluminum fluoride mineralization. Most of the ore minerals crystallized from the silicate melt during the magmatic stage. The accessory cryolites in granites crystallized from the magmatic silicate melt enriched in fluorine. However, cryolites in large veins and lens-like bodies crystallized in the latest stage from the fluorine enriched melt. The zircons from the ores in the aegirine-arfvedsonite granite have been dated at 2055±7Ma. This age is close to the previously published 2066±6Ma zircon age of the aegirine-arfvedsonite granites, suggesting that the formation of the Katugin rare-metal deposit is genetically related to the formation of peralkaline granites. We conclude that Katugin rare-metal granites are anorogenic. They can be related to a Paleoproterozoic (~2.05Ga) mantle plume. As there is no evidence of the 2.05Ga mantle plume in other areas of southern Siberia, we suggest that the Katugin mineralization occurred on the distant allochtonous terrane, which has been accreted to Siberian Craton later.